Effect of temperature on colloids of agricultural soils through dynamic light scattering - Lerma H., Túlio Armando; Combatt., Enrique Miguel; Palencia L., Manuel Salvador (Revista de Ciencias Agrícolas, 2015)
Organic matter and the colloidal fraction are the main soil components affected by indiscriminate bush burning. As a consequence, soil structure deterioration, loss of cation exchange capacity (CEC), and soil fertility reduction occur due to the high temperatures. In contrast, the use of thermal treatment has been proposed as a grounding strategy for clayey soils in civil constructions. However, the effect of temperature on the colloidal fraction has only been assessed in terms of its mechanical properties, while few studies have addressed its effect in relation to agriculturally important properties, such as CEC, structure, and erosion susceptibility. The objective of this study was to study the effect of temperature on the colloidal fraction of agricultural soils through dynamic light scattering (DLS). Two soil samples from the departments of Córdoba and Valle del Cauca were collected and characterized. The colloidal fraction was extracted through a modified Bouyoucos method and subjected to different hermal treatments (from 150°C to 550°C). The samples were characterized according to elemental analysis, FT-IR, and DLS, and their CEC was evaluated. It was concluded that colloidal fraction properties are strongly altered by the effect of temperature. Furthermore, a decrease in CEC (from 76 to 35 and 103 to 26 cmol(+)/kg soil) and an increase in particle size (from 639 ± 165 to 1250 ±435 and 606 ± 102 to 1540 ± 320) were observed for S-Cordoba and S-Valle, respectively; in addition to the elimination of organic matter.